Kenali Tanda Ternak Sehat dan Pembuatan Silase sebagai Upaya Ketahanan Pangan di Desa Cibeureum Wetan, Cimalaka, Sumedang - Muhammad Cito Khairel Fauzan; Andin Dwi Fitri Rahayu; Haya Audina Azizia; Klea Chandra; Olivia Karo; Jonathan Felix Raynar; Fauzan Fajari; Dythia Asma Nadia; Sudrajat, Agus Oman (Jurnal Pusat Inovasi Masyarakat, 2025)
This community service activity aimed to enhance the knowledge and skills of goat and sheep farmers in Cibeureum Wetan Village in early detection of livestock health and processing forage feed into silage to support year-round feed sustainability. The implementation method was participatory, involving counseling sessions, demonstrations, and hands-on practice in making silage using local materials and conducting basic livestock health checks. The participants consisted of 27 farmers from three hamlets, with materials delivered by resource persons from the Regional Technical Implementation Unit (UPTD) of Sumedang Regency and students from the IPB University KKN-T Innovation program. The effectiveness of the activity was evaluated through a 10-question pre-test and post-test to measure knowledge improvement, as well as observation of participants’ practical skills. The evaluation results showed an average score increase of 6.92 points (8.25%) from the initial score, along with improved participants’ skills in conducting livestock health examinations and preparing silage according to procedures. This activity also generated sustainability initiatives, including the establishment of a small-scale silage production unit, utilization of local raw materials, and collaboration with external partners. In conclusion, the training successfully increased participants’ knowledge, improved their technical competencies, and created new entrepreneurial opportunities that support food security in the village.